Evaluation of the Anti-Infectious Activity of the Complex Based on Quantum Dots InP / ZnSe / ZnS 650 and Tobramycin Against Pseudomonas Aeruginosa Infection of the Cornea. Experimental Research - O. V. Shilovskikh; V. O. Ponomarev; V. N. Kazaykin; K. A. Tkachenko; A. S. Vokhmintsev; I. A. Weinstein; S. M. Rozanova; M. V. Kirf; S. V. Marysheva (Oftalʹmologiâ)
Microbial keratitis (MK) is a homogeneous group of diseases accompanied by loss of the corneal epithelium, stromal leukocyte infiltration and/or destructive tissue breakdown, occurring when the protective mechanisms of the ocular surface are disturbed, which require an immediate set of therapeutic measures, including, first of all, massive etiotropic therapy, which is represented, as a rule, by broad-spectrum antibiotics (AB) and anti-inflammatory drugs. One of the most threatening MK pathogens is P. aeruginosa (PA) (Pseudomonas aeruginosa). Multiple drug resistance, the highest pathogenicity, numerous RA virulence factors dictate the need to search for new highly effective methods to combat MC, in the etiological structure of which RA dominates. The most promising direction in this area is the use of artificial fluorophores, in particular quantum dots (QDs). The objective of this study was to evaluate the anti-infectious activity of the complex based on InP/ZnSe/ZnS 650 quantum dots and Tobramycin against Pseudomonas aeruginosa infection of the cornea. As an object of study, laboratory New Zealand rabbits (No. 6) were studied — 2 females, 4 males, which were induced bacterial keratitis by introducing a nosocomial Ps strain. aeruginosa in the structure of the cornea. The following antimicrobial agents were used: Tobramycin solution 5 ml for epibulbar application and a bioconjugate based on QD InP/ZnSe/ZnS 650 and tobramycin. Laboratory animals were divided into 2 groups. Rabbits of the 1st group, after the manifestation of the clinical picture of microbial keratitis, received instillations of tobramycin drops into the conjunctival sac every 2 hours for 3 days with a complete absence of positive clinical dynamics and a subsequent transition from day 4 in order to anatomically preserve the eyeball to instillations of the CT InP/ZnSe/ZnS complex 650 + Tobramycin. Rabbits of the 2nd group received instillations of the CT + Tobramycin complex and showed positive dynamics in relation to the regression of symptoms from the 2nd day of therapy. As methods of dynamic observation, photoregistration of the anterior segment with fluorescein staining and optical coherence tomography of the anterior segment were used. A clinical experiment has demonstrated the highest efficiency of the InP/ZnSe/ZnS 650 + Tobramycin complex in relation to Pseudomonas aeruginosa strain resistant to Tobramycin monotherapy.